(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Nadtoka O. F., Martyniuk T. S. Application of activity approach as one the aspects of study of geography teaching methods. The article deals with issues relating to the problems of methodological principles of geography teaching based on activity approach. They are based on rethinking the role of teachers and students in geography teaching at comprehensive schools. The results of activity approach implementation in education are gain in experience of practical and research activities, the formation of personal development through its own learning path, the development of emotional and value attitude to geographical knowledge; development of key and subject competences on the basis of students’ ability to self-education, critical and time perspective thinking. All the above mentioned is caused by need of adequate reflection of the orresponding geographical picture of the world in student’s consciousness.